Integrating Generative and Aspect-Oriented Technologies - Kulesza, Uirá; Garcia, Alessandro; Lucena, Carlos; Staa, Arndt von (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2004)
Over the last years, two new software engineering approaches have been proposed: generative programming and aspect-oriented software development. Generative programming addresses the study and definition of methods and tools that enable the automatic production of system families from a high-level specification. Aspect-oriented software development has been proposed as a technique for improving separation of concerns in the construction of OO software and supporting improved reusability and ease of evolution. The use of aspect-oriented techniques in a definition of a generative approach can bring benefits to the modeling and generation of crosscutting features since early development stages. This paper presents our experience in the definition of an aspect-oriented generative approach. The proposed approach explores the multi-agent systems domain to enable the code generation of agent architectures.